SMARTPHONE ADDICTION AND ITS RELATIONSHIP WITH PSYCHOLOGICAL HEALTH AMONG STUDENTS OF A MEDICAL SCHOOL IN EAST COAST MALAYSIA - AZWANIS ABDUL HADI; HAWARI MUSYIR MOHD NAWAWI; NURAFIFAH SHAMSURI; NURUL NAJIHAH RAHIM; HAFIZAH PASI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Smartphones have now become a common and almost essential tool in our daily living activities. Students are among those who use smartphones regularly, which could lead to addiction if overused. This study aims to measure the prevalence of smartphone addiction and its relationship with psychological health among clinical year medical students in International Islamic University Malaysia (IIUM), Kuantan. Methods: A total of 226 medical students in their clinical years were recruited through quota sampling method. The students filled in a four-part online-based questionnaire consisted of questions on sociodemographic characteristics, smartphone usage information, smartphone addiction scale-short version, and WHOQOL-BREF. Data were analyzed using IBM SPSS Statistics. Results: The prevalence of smartphone addiction among clinical year medical students in IIUM was 51%. Bivariate analysis showed that the majority of students chose social networking as their primary purpose of using a smartphone, and this was significantly associated with smartphone addiction (p=0.037). Following multiple logistic regression analysis, students who had chosen games as their primary purpose of smartphone users are 88% less likely to be related with smartphone addiction (p=0.009, 95% CI: 0.025–0.595) as compared to those who used it for academic performance tasks. Students who were not addicted to smartphones reported significantly better psychological quality of life compared to those who were addicted (p<0.001). Conclusion: Half of IIUM’s medical students in clinical years was found to have smartphone addiction, and those with smartphone addiction had poor psychological health. Immediate intervention such as creating awareness in the campus is important in curbing this problem.